On Topological Properties of Metrics Defined via Generalized "Linking Construction". (21st November 2017) - Borkowski, Marcin; Bugajewski, Dariusz; Burchardt, Adam
Abstract : We analyze topological properties of metric spaces obtained by using Száz's construction, which we used to call generalized "linking construction." In particular, we provide necessary and sufficient conditions for completeness of metric spaces obtained in this way. Moreover, we examine the relation between Száz's construction and the "linking construction." A particular attention is drawn to the "floor" metric, the analysis of which provides some interesting observations.